Genetic polymorphism of cassava within the Republic of Benin detected with RAPD markers - Tonukari, N.J.; Thottappilly, G.; Ng, N.Q.; Mignouna, H. (1997)
A knowledge of the extent of genetic variation in a crop is a prerequisite for its improvement. In cassava (Manihot esculenta Crantz) such knowledge is lacking especially at the DNA level. The genetic variation among 28 cassava varieties collected from different locations in the Republic of Benin was investigated using random amplified polymorphic DNA (RAPD). A set of 10 random sequence 10-mer primers out of 100 that were screened detected polymorphisms and generated 78 amplified DNA bands. Based on an unweighted pair group method with arithmetic averages (UPGMA) cluster analysis, the accessions were categorised into 6 groups. The results, summarised in a dendrogram, show the genetic diversity among this cassava germplasm.